2011
DOI: 10.1371/journal.pone.0024642
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Functional Network Connectivity: An EEG-fMRI Fusion in Network Space

Abstract: EEG and fMRI recordings measure the functional activity of multiple coherent networks distributed in the cerebral cortex. Identifying network interaction from the complementary neuroelectric and hemodynamic signals may help to explain the complex relationships between different brain regions. In this paper, multimodal functional network connectivity (mFNC) is proposed for the fusion of EEG and fMRI in network space. First, functional networks (FNs) are extracted using spatial independent component analysis (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 53 publications
0
31
0
1
Order By: Relevance
“…The beta rhythm is generally associated with a state of cortical activation, and up to now few reports have described its changes under intermittent visual stimulation [23]. In this study GC and TE measured the total amount of information transfer across electrodes in any direction, which may be interpreted as a sign of activation of different interacting functional networks [24]. In particular, we found that strong causal connections were activated in migraine with aura across posterior and anterior electrodes.…”
Section: Discussionmentioning
confidence: 56%
“…The beta rhythm is generally associated with a state of cortical activation, and up to now few reports have described its changes under intermittent visual stimulation [23]. In this study GC and TE measured the total amount of information transfer across electrodes in any direction, which may be interpreted as a sign of activation of different interacting functional networks [24]. In particular, we found that strong causal connections were activated in migraine with aura across posterior and anterior electrodes.…”
Section: Discussionmentioning
confidence: 56%
“…For example, it was shown that very different graphs are obtained from MEG and fMRI data, even when the graph structure learning algorithm is the same [49]. This indicates that interpretation of brain graphs and their properties must always consider the limitations of the modality used, but also that multimodal graph analysis methods might bring additional insight [50].…”
Section: Clinical Neurosciencementioning
confidence: 99%
“…Similarly, the voxel correlations in fMRI and DTI are defined differently, 13 requiring different edge types. The ability to declare edge and vertex types dynamically in Python allows co-analysis of different brain networks and overcomes the limitations of using a single modality [28], and we plan to leverage our described methodology for forthcoming investigations of computational neuropathology.…”
Section: Motivationmentioning
confidence: 99%